Automated peritoneal dialysis as a cost-effective urgent-start dialysis option for ESRD patients: A prospective cohort study. Issue 8 (August 2022) - Jin, Haijiao; Lu, Renhua; Lv, Shifan; Wang, Ling; Mou, Shan; Zhang, Minfang; Wang, Qin; Pang, Huihua; Yan, Hao; Li, Zhenyuan; Che, Miaoling; Shen, Jianxiao; et al.
Background: Several studies have reported the feasibility of urgent-start peritoneal dialysis (PD) as an alternative to hemodialysis (HD) using a central venous catheter (CVC). However, the cost-effectiveness of automated peritoneal dialysis (APD) as an urgent-start dialysis modality has not been directly evaluated, especially in China. Methods: We prospectively enrolled patients with end-stage renal disease (ESRD) who required urgent-start dialysis at a single center from March 2019 to November 2020. Patients were grouped according to their urgent-start dialysis modality (APD and HD). Urgent-start dialysis conducted until 14 days after PD catheter insertion. Then, PD was maintained. Each patient was followed until July 2021 or death or loss to follow-up. The primary outcome was the incidence of short-term dialysis-related complications. The secondary outcome was the cost and duration of the initial hospitalization. Technique survival, peritonitis-free or bacteriamia-free survival and patient survival were also compared. Results: Sixty-eight patients were included in the study, of whom 36 (52.9%) patients were in APD group. Mean follow-up duration was 20.1 months. Compared with the HD group, the APD group had significantly fewer short-term dialysis-related complications. The cost of initial hospitalization was also significantly lower in APD patients. There was no significant difference between APD and HD patients with respect to duration of the initial hospitalization, technique survival rate, peritonitis-free or bacteriemia-free survival rate, and patient survival rate. Conclusion: Among ESRD patients with an urgent need for dialysis, APD as urgent-start dialysis modality, compared with HD using a CVC, resulted in fewer short-term dialysis-related complications and lower cost.